Pengaruh Nilai yang Dirasakan Pelanggan (Functional, Social, Emotional dan Epistemic Value) Terhadap Niat Pelanggan untuk Menggunakan Internet sebagai Platform Ritel - Nilasari, B Medina (Manajemen Bisnis Kompetensi, 2018)
This study investigates the effect of customer’s value (functional, social, emotional and epistemic value) through customer intention to use the internet as a retailing platform. The proposed hypotheses were tested with a sample of 149 students of Trisakti University. The results indicate that customer intention to use the internet as a retailing platform is positively effected by functional, emotional (positive) and epistemic value. The results suggested that every marketing manager should focus on functional, emotional (positive) and epistemic value in making marketing strategy, because the values can effect customer intention to use internet as a retailing platform. Keywords: customer’s value, emotional, epistemic, customer intention, retailing platform